The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1089/neu.2017.5232
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Traumatic Intracranial Hemorrhage in Head-Injured Older Adults Transported by EMS with and without Anticoagulant or Antiplatelet Use

Abstract: Field triage guidelines recommend transport of head-injured patients on anticoagulants or antiplatelets to a higher-level trauma center based on studies suggesting a high incidence of traumatic intracranial hemorrhage (tICH). We compared the incidence of tICH in older adults transported by EMS with and without anticoagulation or antiplatelet use and evaluated the accuracies of different sets of field triage criteria to identify tICH. This was a prospective, observational study at 5 EMS agencies and 11 hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 39 publications
3
49
0
1
Order By: Relevance
“…7 Prior studies have also shown that current field triage guidelines are not accurate in predicting trauma center need in this population. [8][9][10]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Prior studies have also shown that current field triage guidelines are not accurate in predicting trauma center need in this population. [8][9][10]…”
Section: Discussionmentioning
confidence: 99%
“…Older adults with head injury often have minor mechanisms of injury, such as falls from standing height, yet have significant traumatic intracranial hemorrhage . Prior studies have also shown that current field triage guidelines are not accurate in predicting trauma center need in this population …”
Section: Introductionmentioning
confidence: 99%
“…To date, specific recommendations are missing for low‐energy trauma in older patients such as ground‐level falls with or without anticoagulation or antiplatelet treatments and equivocal clinical signs of traumatic brain injury. Current studies on these particular patients are heterogeneous and bear some limitations, such as missing control group, small sample sizes, or lacking information about injury severity …”
mentioning
confidence: 99%
“…The vast majority were ground level falls. Previous research has reported a 2.3% rate of ICH in low‐risk head injury patients (Glasgow Coma Scale of 15, no neurologic findings, no visible wounds, and no coagulation diseases or medications) and 11% in hospitalized head trauma patients …”
mentioning
confidence: 97%
“…Some studies suggest that the incidence of ICH is more common and outcomes are worse when they occur in patients on anticoagulation . Others report that the incidence of ICH with anticoagulation is unchanged . These studies, in general, are limited as most are retrospective, have relatively low numbers of subjects, or have other methodologic limitations.…”
mentioning
confidence: 99%